Research, applications, and interventions for children and adolescents : a positive psychology perspective - Linley, P. Alex; Proctor, Carmel (Springer Netherlands, 2013)
This book presents recent positive psychological research, applications and interventions being used among adolescents and children. Currently there is a wave of change occurring whereby educators, and others working with children and adolescents, are beginning to recognize the benefits of looking at well-being from a positive perspective, specifically the integration of positive psychological theory into the school curriculum in order to improve student well-being. Moreover, although the positive psychological field has grown tremendously since its inception, there remains an imbalance in the publication of research findings, applications, and interventions among children and adolescents in comparison to adults. This book fills the need for a reference to this valuable information and benefits a wide range of professionals, including educators, clinicians, psychologists, students, and many other working with children and adolescents.